EFEKTIFITAS MODEL PROJECT BASED LEARNING BERBANTUAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR IPAS MATERI ORGAN PERNAPASAN MANUSIA DAN FUNGSINYA KELAS 5 SEKOLAH DASAR NEGERI WATUPECAH REMBANG - Sholikhatun Nikmah; Ifa Seftia Rakhma Widiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the Project Based Learningmodel on science learning outcomes (IPAS) regarding the topic of humanrespiratory organs and their functions among fifth-grade students at SDNWatupecah, Rembang Regency. This research is a quantitative study using a one-group pretest-posttest design. The population in this study consisted of all fifth-grade students at SDN Watupecah in the 2024/2025 academic year, with asample of 20 students selected using non-probability sampling with a simplerandom sampling technique. Data collection was carried out through interviews,observation, tests, and documentation. The results of the normality test indicatedthat the pretest and posttest data were normally distributed. The t-test resultsshowed that the average pretest score was 56.55 and the average posttest scorewas 80.4, with N = 20. The calculated t-value was 4.024, while the critical t-valueat a significance level of 0.05 with 19 degrees of freedom was 2.093. Since thecalculated t-value is greater than the critical t-value (t_calculated > t_table), thenull hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted.Therefore, it can be concluded that the Project Based Learning model is effectivein improving science learning outcomes on the topic of human respiratory organsand their functions among fifth-grade students at SDN Watupecah, RembangRegency. Based on the results, the researcher suggests that the Project BasedLearning model can be used as a variation in teaching, as its implementationcreates an active, enjoyable, and effective learning environment that enhancesstudent achievement.